Pathophysiological Mechanisms and Experimental Pharmacotherapy for L-Dopa-Induced Dyskinesia - Fabbrini A; Guerra A (Dove Medical Press, 2021)
Andrea Fabbrini,1 Andrea Guerra2 1Department of Human Neurosciences, Sapienza University of Rome, Rome, Italy; 2IRCCS Neuromed, Pozzilli, IS, ItalyCorrespondence: Andrea GuerraIRCCS Neuromed, Sapienza University of Rome, Via Atinense 18, Pozzilli, 86077, IS, ItalyEmail andrea.guerra@uniroma1.itAbstract: L-dopa-induced dyskinesia (LID) is the most frequent motor complication associated with chronic L-dopa treatment in Parkinson’s disease (PD). Recent advances in the understanding of the pathophysiological mechanisms underlying LID suggest that abnormalities in multiple neurotransmitter systems, in addition to dopaminergic nigrostriatal denervation and altered dopamine release and reuptake dynamics at the synaptic level, are involved in LID development. Increased knowledge of neurobiological LID substrates has led to the development of several drug candidates to alleviate this motor complication. However, with the exception of amantadine, none of the pharmacological therapies tested in humans have demonstrated clinically relevant beneficial effects. Therefore, LID management is still one of the most challenging problems in the treatment of PD patients. In this review, we first describe the known pathophysiological mechanisms of LID. We then provide an updated report of experimental pharmacotherapies tested in clinical trials of PD patients and drugs currently under study to alleviate LID. Finally, we discuss available pharmacological LID treatment approaches and offer our opinion of possible issues to be clarified and future therapeutic strategies.Keywords: dyskinesia, L-dopa, Parkinson’s disease, glutamate, serotonin, therapy